2021
DOI: 10.3390/jcm10153391
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Incidence Rate of Hospitalizations Due to AIDS-Defining Conditions but Not to Non-AIDS Conditions in PLWHIV on cART in 2008–2018 in Italy

Abstract: Background: We aimed to describe the change in the incidence and causes of hospitalization between 2008 and 2018 among persons living with HIV (PLWHIV) who started antiretroviral therapy (ART) from 2008 onwards in Italy. Methods: We included participants in the ICONA (Italian Cohort Naïve Antiretrovirals) cohort who started ART in 2008. All the hospitalizations occurring during the first 30 days from the start of ART were excluded. Hospitalizations were classified as due to: AIDS-defining conditions (ADC), non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Whereas the Canadian study found a lower risk for HIV-related and all-cause hospitalisation in migrants compared with non-migrants, 37 the Italian study found some evidence that non-Italian nationality was associated with an increased risk of all-cause and non-AIDS-related hospitalisation but not with AIDS-defining hospitalisation. 3 A previous ART-CC analysis found lower mortality in migrants from sub-Saharan Africa, Asia, or other western (ie, Europe [ for the North American analysis], the USA and Canada [ for the European analysis], Australia, and New Zealand) countries but not from Latin America or the Middle Eastern or north African regions. 38 There are two competing potential hypotheses.…”
Section: Discussionmentioning
confidence: 96%
“…Whereas the Canadian study found a lower risk for HIV-related and all-cause hospitalisation in migrants compared with non-migrants, 37 the Italian study found some evidence that non-Italian nationality was associated with an increased risk of all-cause and non-AIDS-related hospitalisation but not with AIDS-defining hospitalisation. 3 A previous ART-CC analysis found lower mortality in migrants from sub-Saharan Africa, Asia, or other western (ie, Europe [ for the North American analysis], the USA and Canada [ for the European analysis], Australia, and New Zealand) countries but not from Latin America or the Middle Eastern or north African regions. 38 There are two competing potential hypotheses.…”
Section: Discussionmentioning
confidence: 96%
“…A study on a European population of HIV-infected patients from 2001 to 2009 reported considerable mortality associated with non-AIDS events, exceeding that of AIDS events. In high-income countries, nADEs have become the most common reason for hospitalization, and the rates for nADE-related hospitalizations have remained stable or increased over the past two decades ( 32 35 ). Our adjusted analysis showed that the nADE-related hospitalization rates were low and stable and mainly happened in ART-experienced patients.…”
Section: Discussionmentioning
confidence: 99%